Volatile and fixed composition of sulphite-free white wines obtained after fermentation in the presence of chitosan. (July 2018) - Castro-Marín, Antonio; Buglia, Ana Gabriela; Riponi, Claudio; Chinnici, Fabio
Abstract: Consumers are increasingly interested in healthier wines containing reduced levels or totally absent of sulphites. In the present investigation distinct fermentations of white musts either in the presence of chitosan or sulphur dioxide were carried out in order to compare the volatile and fixed composition of the wines produced, and evaluate the impact of chitosan as an alternative to sulphur dioxide. Chitosan promoted a 24 h extended lag-phase and diminished the titratable acidity of wines by about 1 g L −1 as a consequence of the absorption of tartaric and malic acids onto the polymer surface. The volatile composition of wines was analysed at the end of the alcoholic fermentation and then after 12 months of storage in glass bottle. Hexanoic, octanoic and decanoic acids were significantly higher in chitosan added wines, which further contained an increased amount of ethyl and acetate esters. Results demonstrated that, when added before the alcoholic fermentation, chitosan may affect both the acidic and volatile composition of wines, likely due to its polycationic behaviour and interaction with yeast wall constituents. This also suggests that attention to wine acidic balance should be paid before its use in other vinification steps such as must clarification or wine fining. Highlights: Chitosan interferes with Saccharomyces cerevisiae cell growth extending the lag-phase. Grape must organic acids are partially absorbed by chitosan during fermentation. Chitosan increase the contents of volatile esters and acids in wines. The alteration of yeast cell permeability by chitosan is proposed.